2019
DOI: 10.1002/hyp.13539
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of soil pore water extraction methods for stable isotope analysis and interpretation of hillslope runoff sources

Abstract: Intercomparison of soil pore water extraction methods for stable isotope analysis has been a focus of recent studies in relation to plant source waters, which found a wide isotopic variance depending on the extraction method. Few studies have yet explored extraction effects for mobile pore waters that relate to hillslope runoff. This is because it is extremely difficult in natural systems to control the boundary conditions in order to assess and compare impacts of pore water extraction on resulting hillslope f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…The fraction of soil water sampled by different extraction methods is currently one of the main questions faced by the ecohydrological research community (Berry et al, 2018;Penna et al, 2018;Sprenger et al, 2018;Orlowski et al, 2019). In comparison to the direct water vapor equilibration method, cryogenic vacuum extraction can likely also access hygroscopic and biologically bound water (Koeniger et al, 2011;Sprenger et al, 2015;Orlowski et al, 2016b).…”
Section: Methodological Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fraction of soil water sampled by different extraction methods is currently one of the main questions faced by the ecohydrological research community (Berry et al, 2018;Penna et al, 2018;Sprenger et al, 2018;Orlowski et al, 2019). In comparison to the direct water vapor equilibration method, cryogenic vacuum extraction can likely also access hygroscopic and biologically bound water (Koeniger et al, 2011;Sprenger et al, 2015;Orlowski et al, 2016b).…”
Section: Methodological Differencesmentioning
confidence: 99%
“…Berry et al (2018) addressed the methodological state of the art in stable isotope ecohydrology as "shotgun" or "snapshot methods", referring to the lack of continuous measurements. Laboratory based water extraction methods are currently highly debated due to their inaccuracy and non-comparability of the obtained isotope results (Orlowski et al, 2019). Issues observed with laboratory based methods are mainly due to interferences with soil texture, water contents, interactions with cations, and the different pore spaces that may or may not be extracted via the different approaches (Meißner et al, 2014;Oerter et al, 2014;Orlowski et al, 2016bOrlowski et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Artificial effects (ART in Figure 1) mainly include soil and xylem water field sampling and extraction methods as well as instrumental measurement uncertainty in laboratory analysis, as follows: a) Different methods for soil water sampling and extraction, such as tension lysimeters and cryogenic vacuum distillation returning different isotopic composition from the same sample (Geris et al, 2015;Orlowski et al, 2016Orlowski et al, , 2018Orlowski et al, , 2019. b) Different methods for plant water sampling and extraction such as cryogenic vacuum distillation, Scholander-type pressure chamber, and other destructive methods possibly producing artifacts and returning different isotope values (Thoma et al, 2018;Fischer et al, 2019;Zuecco et al, 2020), preferentially affecting 2 H rather than 18 O values (Chen et al, 2020).…”
Section: Heterogeneity and Uncertainty In Isotope-based Estimates Of mentioning
confidence: 99%
“…The effective failure rate is at or below 5% when soil samples are double bagged (Wassenaar et al, 2008), which also avoids interlaboratory isotope contamination (Mueller et al, 2014;Orlowski, Pratt, & McDonnell, 2016) and allows the soil samples to be processed with less potential to evaporate compared with isotope-ratio mass spectrometry methods (Wassenaar et al, 2008). Work by Orlowski et al (2016) found that conventional methods, such as cryogenic distillation, may be prone to large offsets between measurements and reference waters, and assessments of the errors within our data show our approach is consistent with a recent methodological assessment study (Wang, Si, Pratt, Li, & Ma, 2020), which reported measurement errors on spiked samples of known isotopic composition. Sample handling and analysis was maintained consistent across all treatments and locations; thus, differences between samples are expected to be caused by field conditions and not normal laboratory procedures.…”
Section: Laboratory Analysis and Post-processingmentioning
confidence: 99%